2018
DOI: 10.1055/s-0038-1627452
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive, Isolated Tricuspid Valve Redo Surgery: A Safety and Outcome Analysis

Abstract: Minimally invasive, isolated TV surgery as reoperation without caval occlusion and on the beating heart can be safe and may improve clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The improvement in the NYHA functional class may be explained in part by the concomitant procedures, but there is increasing evidence that TVR alone improves NYHA functional class. 13 Several studies have shown that FTR should be addressed during an initial left-sided surgery because TR may be progressive and because late surgery for uncorrected FTR has been shown to confer increased risk. 5 Furthermore, concomitant TVR during an initial procedure does not affect operative mortality, 14,15 and it is increasingly supported by published guidelines despite the lack of randomized data proving its benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the NYHA functional class may be explained in part by the concomitant procedures, but there is increasing evidence that TVR alone improves NYHA functional class. 13 Several studies have shown that FTR should be addressed during an initial left-sided surgery because TR may be progressive and because late surgery for uncorrected FTR has been shown to confer increased risk. 5 Furthermore, concomitant TVR during an initial procedure does not affect operative mortality, 14,15 and it is increasingly supported by published guidelines despite the lack of randomized data proving its benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the freedom from jugular cannulation, our modified inferior caval drainage technique can minimize the anesthetic and preoperative preparing time and decrease the iatrogenic injuries caused by jugular cannulation, for instance, jugular hemotoma, pneumothorax, or hemothorax. 7,12,27 Moreover, a better cosmetic outcome can be acquired thanks to the avoiding of right cervical incision for cannulation, which is notable and may cause keloid and pigmentation. 28 With the evolution of the innovative trans-catheter intervention of TV, TV repair or replacement will be performed by more and more minimally invasive method or maybe even incisionless in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] With the development of minimally invasive cardiac surgery in this decade, a great number of reports have shown better clinical outcomes of the minimally invasive right anterior lateral thoracotomy surgery than traditional median sternotomy surgery for reoperative isolated TV operations. [4][5][6][7] However, the operative visual field through mini-thoracotomy was quite limited until the application totally video-assisted thoracoscopic cardiac surgery, which can bring much better exposure for TV in patients with previous median cardiac surgery than right mini-thoracotomy. As for the intervention of reoperative isolated TR, TV repair can provide better clinical outcomes and less thromboembolic events than TV replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the common occurrence of PH in patients undergoing TVR/TVr, there is lack of invasive hemodynamic characterization of PH. Prior studies describe PH in patients undergoing TVR/TVr predominantly based on estimated systolic pulmonary artery pressure from echocardiograms (7,8,10). However, echocardiography can significantly underestimate or overestimate pulmonary artery pressures (26).…”
Section: Right Ventricular Function and Pulmonary Hypertensionmentioning
confidence: 99%
“…In addition, the sudden increase in RV preload after TVR/TVr (with the correction of the "pop-off" mechanism) can worsen RV function. However, the threshold of PH that is associated with increased mortality after TVR/TVr is unclear (7)(8)(9)(10). This is because the current literature on the impact of PH on outcomes after TVR/TVr is limited by the lack of invasive hemodynamic measurements.…”
Section: Introductionmentioning
confidence: 99%